Association between Self-Reported Habitual Snoring and Diabetes Mellitus: A Systemic Review and Meta-Analysis. (19th January 2016) - Xiong, Xiaolu; Zhong, Anyuan; Xu, Huajun; Wang, Chun
Abstract : Aim . Several studies have reported an association between self-reported habitual snoring and diabetes mellitus (DM); however, the results are inconsistent. Methods . Electronic databases including PubMed and EMBASE were searched. Odds ratios (ORs) and 95% confidence intervals (CIs) were used to assess the strength of the association between snoring and DM using a random-effects model. Heterogeneity, subgroup, and sensitivity analyses were also evaluated. Begg's, Egger's tests and funnel plots were used to evaluate publication bias. Results . A total of eight studies (six cross sectional and two prospective cohort studies) pooling 101, 246 participants were included. Of the six cross sectional studies, the summary OR and 95% CI of DM in individuals that snore compared with nonsnorers were 1.37 (95% CI: 1.20–1.57, p < 0.001 ). There was no heterogeneity across the included studies (I 2 = 2.9 %, p = 0.408 ). When stratified by gender, the pooled OR (95% CI) was 1.59 (1.20–2.11) in females (n = 12298 ), and 0.89 (0.65–1.22) in males (n = 4276 ). Of the two prospective studies, the pooled RR was 1.65 (95% CI, 1.30–2.08). Conclusions . Self-reported habitual snoring is statistically associated with DM in females, but not in males. This meta-analysis indicates a need to paying attention to the effect of snoring on the occurrence of DM in females.